2020
DOI: 10.1101/2020.09.22.20192443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reinfection with SARS-CoV-2 and Failure of Humoral Immunity: a case report

Abstract: Recovery from COVID-19 is associated with production of anti-SARS-CoV-2 antibodies, but it is uncertain whether these confer immunity. We describe viral RNA shedding duration in hospitalized patients and identify patients with recurrent shedding. We sequenced viruses from two distinct episodes of symptomatic COVID-19 separated by 144 days in a single patient, to conclusively describe reinfection with a new strain harboring the spike variant D614G. With antibody and B cell analytics, we show correlates of adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
108
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 25 publications
1
108
0
1
Order By: Relevance
“…4 It is the most comprehensive studied as it documented seroconversion following the first infection, showed drastically different viral genomes with 34 nucleotide differences, and ruled out errors of samples by techniques commonly used for forensic identifications. The present case adds to 13 previously reported cases of re-infection with a different SARS-CoV-2 strain that occurred in China, Belgium, the Netherlands, India, Ecuador and the USA 2 , 5 , 6 , 7 , 8 , 9 (Supplementary Table S2) documented with varying degrees of robustness (Supplementary Table S3). Mean age (± standard deviation) of the 14 cases was 40±20 years (range, 24-89), and patients were mostly immunocompetent individuals (in 12 cases (86%)).…”
supporting
confidence: 61%
“…4 It is the most comprehensive studied as it documented seroconversion following the first infection, showed drastically different viral genomes with 34 nucleotide differences, and ruled out errors of samples by techniques commonly used for forensic identifications. The present case adds to 13 previously reported cases of re-infection with a different SARS-CoV-2 strain that occurred in China, Belgium, the Netherlands, India, Ecuador and the USA 2 , 5 , 6 , 7 , 8 , 9 (Supplementary Table S2) documented with varying degrees of robustness (Supplementary Table S3). Mean age (± standard deviation) of the 14 cases was 40±20 years (range, 24-89), and patients were mostly immunocompetent individuals (in 12 cases (86%)).…”
supporting
confidence: 61%
“…Early discussions raised concern of possible antigenic drift, suggesting that vaccines targeting S(D614) may offer limited protection against viruses with S(G614) and that antibodies in exposed individuals would not offer cross-protection [ 64 ]. Indeed, though reinfections have been reported with two independent isolates harboring the same S protein variant [ 65 ], recent case reports identified first infection events with D614 virus followed by reinfection with G614 virus [ 66 , 67 ]. However, many studies have shown that humoral immunity is likely protective against both variants.…”
Section: Introductionmentioning
confidence: 99%
“…To date, among the few reinfection cases reported, one study found the humoral immune response to be defective during the second infection, suggesting that a failure of the humoral response during the first infection may account for susceptibility to reinfection ( 42 ). In addition, Chen et al demonstrate a positive correlation between the magnitude of NAb titres and disease severity but also report immense heterogeneity between the NAbs generated—with 80.7% patients producing S1 specific NAbs and only 40% patients producing NAbs to both S1 and S2.…”
Section: Humoral Protectionmentioning
confidence: 99%
“…The first challenge studies in macaques showed that SARS-CoV-2 infection may result in the development of protective immunity, when the animals were challenged soon after resolution of the primary infection (39,40). However, a number of cases of reinfection in humans have now been reported a few months after initial infection, challenging the idea of long-lasting protective immunity (41)(42)(43)(44)(45)(46)(47).…”
Section: Introductionmentioning
confidence: 99%